Frugal Living : Perspektif Generasi Z Melalui Pendekatan Kualitatif - Hasanah, Naimatul; Badria, Nuril (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2024)
This research aims to delve into the perspective of Z’S Generation on frugal living through a qualitative approach. Frugal living, or the thrifty lifestyle, has become an intriguing topic amidst the complexity of modern economics. This study employs in-depth interviews and content analysis to understand the views, attitudes, and practices of Generation Z regarding frugal living. The findings indicate that Generation Z has a strong understanding of the importance of managing finances wisely. They associate frugal living with sustainability and social responsibility concepts. However, there are challenges in implementing frugal living, including high consumption temptations and pressures from social environments. This research provides valuable insights into how factors such as peer influence and access to information through social media affect the financial decisions of Generation Z.